EFFECT OF MOBILE PHASE COMPOSITION ON THE SELECTIVITY OF CHROMATOGRAPHY COLUMNS WHICH USE POLYPYRROLE AS THE STATIONARY PHASE - Hawick Chriswanto (Testing Center for Oil and Gas LEMIGAS, 2002)
Chromatography columns packed with polymeric stationary phase have been prepared. The packing materials were prepared by depositing polypyrrole chloride or polypyrrole dodecylsulfate onto silica particles. The deposition was accomplished by chemical oxidative polymerisation. Chromatographic selectivity of the columns was examined under reversed-phase condition using pairs of test compounds with known functionalities as the probes. The results showed that if hydrophobic interactions were dominant, the selectivity increased with decreasing in organic fraction in the mobile phase, and vise versa.